Nonverbal behavior in clinical settings - Philippot, Pierre, 1960-; Feldman, Robert S. (Robert Stephen), 1947-; Coats, Erik J., 1968- (Series in affective science., 2003)
The volume is organized into three sections: " Nonverbal Behavior in Regulatory and Clinical Processes"; "Nonverbal Behavior in Negative Life Events"; and, "Nonverbal Behavior in Specific Clinical Conditions,"